Correlation between serum zinc level and simple febrile seizure in children - Lusiana Margaretha; Nurhayati Masloman (Paediatrica Indonesiana, 2010)
Background Simple febrile seizure is the most common form of seizure which occurs during childhood period. Zinc, one of microelements in human body, has an important role in central nervous system formation.Objectives To find out serum zinc level in simple febrile seizure patients and the correlation between serum zinc level and simplefebrile seizure.Methods This cros-sectional study was conducted at R. D. Kandoll Hospital, Tingkat III Teling Hospital and Pancaran Kasih Hospital, Manado on April 5th - June 15th, 2009.Results Diagnosis for febrile v.ithout seizure patients were 12 with acute respiratory tract infection (ARl), 6 dengue hemorrhagic fever (DHF), 6 acute diarrhea v.ithout dehydration and 1 ARI with DHF, while simple febrile seizure were 19 ARI, five acute diarrhea v.ithout dehydration and one ARI v.ith DHF. There were no significant differences of age, gender and nutritional status in two groups. F amily history of febrile seizure, febrile period and body temperature in two groups were significantly different. Mean serum zinc level in simple febrile seizure and febrile v.ithout seizure were 8.83 Î¼mol/L and 13.72 Î¼mol/L, respectively. Mean serum zinc level in simple febrile seizure children with seizure period <5 minutes, 5-<10 minutes and 10-15 minutes were 10.27 (SD 0.25) Â Î¼mol/L, 9.02 (SD 0.81) ) Î¼mol/L and 6.90 (SD) 0.98 Î¼mol/L, respectively.Conclusions There is correlation between serum zinc level and simple febrile seizure. The lesser serum zinc level, the longer duration of seizure occurs in simple febrile seizure.